Reforming retirement-income systems: Lessons from the recent experiences of OECD countries - John P. Martin; Edward Whitehouse (Institute for the Study of Labor (IZA), 2008)
Reforming pensions looms large over the policy agenda of OECD countries. This is hardly surprising since public spending on pensions accounted on average for 7 per cent of OECD GDP in 2005; and this pension spending effort is set to increase significantly over the coming decades in response to population ageing. Pension policy is indeed challenging and controversial because it involves long-term decisions in the face of numerous short-term political pressures. However, the status quo does not always win out so far as pension reform in concerned: public finance crises and the looming threat of ageing populations have proved effective spurs for reform. As a result, much has been done since the early 1990s to make pension systems fit for the future. Nearly all the 30 OECD countries have made at least some changes to their pension systems in that period. In 16 of them, there have been major reforms that will significantly affect future benefits. The purpose of this paper is to summarise these reforms and highlight the main lessons. Section 1 looks at which countries reformed their pensions systems and which did not. It also examines the fiscal challenges posed by public pensions. Section 2 describes the measures in the reforms themselves. These include, among other things, increases in pension age, changes in the way benefits are calculated and smaller pension increases in retirement than in the past. Section 3 explores the impact of these reforms on future pension entitlements of today's retirees, showing a clear trend to a lower pension promise for todays workers than for past generations. This means that people will need to save more for their own retirement via private pension schemes, an issue examined in Section 4. This is followed in Section 5 by a review of the main outstanding challenges facing pension systems in OECD countries. The final section presents some concluding remarks.
urn:nbn:de:101:1-20080605167
Keywords: H55; 330; reform of public and private pensions; replacement rates; pension wealth; mandatory and voluntary pensions; OECD pension reform challenges; Rentenreform; Gesetzliche Rentenversicherung; Private Rentenversicherung; OECD-Staaten